The Structural Properties of Sn-doped Zinc Oxide Synthesized by Hot-tube Thermal Evaporation - Suhaimi, S; Sakrani, S; Hashim, MA; Nadhrah Md Yatim (Amer Inst Physics, 2024)
The growth of Sn:ZnO nanowires on a silicon substrate using a low thermal evaporation method is reported. A horizontal quartz tube with controlled supply of O-2 gas were used to fabricate the samples where Zn and Sn metal powders were previously mixed and heated at 500 degrees C. This allows the reactant vapours to deposit onto the substrate, which placed at a certain distance from the source materials. The samples were characterized using FESEM, EDX and HRTEM measurements. Randomly oriented nanowires were formed with varying dopant concentrations from 3 to 15 at%. It was observed that from FESEM images, when the dopant concentrations were increased, a hexagonal rod with a wire extended at its end was clearly formed and the best images of nanowires were shown at the highest concentration of 15 at% measuring between 26 to 35 nm and roughly 500 nm in diameter and length respectively. The doping process played an important role in order to alter the morphological properties of Sn: ZnO nanowires. Sn: ZnO nanowires have large potential in many applications such as in selected sensor technology including gaseous sensors, liquid sensors and others.